2011
DOI: 10.1136/bmjqs.2010.042382
|View full text |Cite
|
Sign up to set email alerts
|

Risks and suggestions to prevent falls in geriatric rehabilitation: a participatory approach

Abstract: The findings highlight the complexity of the problem and the value of the approach used to increase our understanding of the issues considering the perspectives of patients, staff and family members. The results are being used to construct context-specific interventions to reduce the rates of falls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 17 publications
1
37
0
Order By: Relevance
“…Some of the residents actually realized that they overestimated their capabilities and described that watching the video helped them to see what they were doing. We found that video-elicitation generated greater participation and discussion than what we experienced in previous studies using interviews alone [17]. Video-elicitation fostered self-awareness, commitment to the research process, and interest in the study results.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Some of the residents actually realized that they overestimated their capabilities and described that watching the video helped them to see what they were doing. We found that video-elicitation generated greater participation and discussion than what we experienced in previous studies using interviews alone [17]. Video-elicitation fostered self-awareness, commitment to the research process, and interest in the study results.…”
Section: Discussionmentioning
confidence: 76%
“…Analysts also watched the transfer videos to gain further contextual information. Transcripts were coded case-by-case following steps used in previous visual studies of safety issues [15][16][17]. The steps included an initial review of the interviews and videos.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Falls not only cause events such as bone fractures and head injuries, but also involve extended hospital stays, increased cost, and reduced mobility led by fear of falling [1][2][3][4][5][6]. It is reported that falls tend to occur as a result of the interactions between patient factors and environment [7].…”
Section: Introductionmentioning
confidence: 99%